Factors affecting purchase intention of vitamins for the prevention of respiratory diseases among Filipinos: Integrating the theories of planned behavior and protection motivation - Chan, Giannina Richelle S. (Animo Repository, 2022)
An unprecedented health crisis caught the whole world off guard last 2020. History has shown that times of crisis often lead to major transformations in society, and behaviors of consumers must be paid attention to. Following the pandemic, individuals have increased their awareness on their health and have begun taking active steps in protecting themselves from getting sick. Using the Theories of Planned Behavior and Protection Motivation, this paper intends to analyze the factors that influence the purchase intention of vitamins in order to prevent respiratory diseases. Vitamins have always been generally accessible, however, their use as an immunity protector have thrust them into the spotlight towards prevention of sickness. The constructs analyzed in this study are TPB’s Attitude, Subjective Norm, and Perceived Behavioral Control, and PMT’s Specific Emotions and Threat and Coping Appraisal. These predictors were tested for their effects on the outcome of Purchase Intent. A cross-sectional structured questionnaire was used in gathering the required data. These were posted in four vitamins points-of-sales around Metro Manila. A total of 411 eligible responses were gathered and results were subjected to various statistical and relational analyses using JASP. Overall, all factors have significant effects on the predictors, albeit to varying degrees. Results showed that Perceived Behavioral Control had the greatest mean score, and the factors of TPB: Attitude, Subjective Norm, and Perceived Behavioral Control had the greatest predictor effect on the Purchase Intention of consumers towards vitamins for the prevention of respiratory diseases. In terms of business implications, these results will be useful in the campaign strategies of business and brand owners to tap into more customers and in turn convert these leads into sales. As the results cannot be representative of the whole population, it is recommended that this study be extended to a larger population with varying demographics. Future studies should be conducted to get more reliable results as time might change the situation.